2009
DOI: 10.1073/pnas.0900189106
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase 3β missplicing contributes to leukemia stem cell generation

Abstract: Recent evidence suggests that a rare population of self-renewing cancer stem cells (CSC) is responsible for cancer progression and therapeutic resistance. Chronic myeloid leukemia (CML) represents an important paradigm for understanding the genetic and epigenetic events involved in CSC production. CML progresses from a chronic phase (CP) in hematopoietic stem cells (HSC) that harbor the BCR-ABL translocation, to blast crisis (BC), characterized by aberrant activation of ␤-catenin within granulocyte-macrophage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
211
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(215 citation statements)
references
References 32 publications
4
211
0
Order By: Relevance
“…It should be pointed out that the leukemogenic splice form of GSK3β could hardly be seen in arrays of unpurified CML blast crisis bone marrow, insofar as the LSCs were only ∼5% of all leukemic marrow cells (200). This provides a very important caution to those who would do epigenetic analyses such as microarrays, RNAseq, chromatin immunoprecipitation, and DNA CpG methylation, to name a few.…”
Section: Cancer Stem Cells and The Therapeutics That Come From Them: mentioning
confidence: 96%
See 2 more Smart Citations
“…It should be pointed out that the leukemogenic splice form of GSK3β could hardly be seen in arrays of unpurified CML blast crisis bone marrow, insofar as the LSCs were only ∼5% of all leukemic marrow cells (200). This provides a very important caution to those who would do epigenetic analyses such as microarrays, RNAseq, chromatin immunoprecipitation, and DNA CpG methylation, to name a few.…”
Section: Cancer Stem Cells and The Therapeutics That Come From Them: mentioning
confidence: 96%
“…We showed that in 4 of 7 patients the activation of the β-catenin pathway occurred because of GMP stage-specific missplicing of GSK3β (200), the cytoplasmic enzyme held in a scaffold complex (with β-catenin, APC, and axin), which phosphorylates β-catenin to tag it for ubiquitination and cytoplasmic proteasomal destruction. The GMP-LSC splice form was uniformly lacking exon 8, encoding the kinase domain, and this was the only splice form in the GMP LSC (200). Both HSCs and Lin + blast cell progeny of the LSCs expressed the splice forms containing exon 8 (200).…”
Section: Cancer Stem Cells and The Therapeutics That Come From Them: mentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41] The variable, but generally long, phase that precedes the diagnosis of chronic phase CML also suggests a high variability in the precise stage of the disease when the diagnosis will be made. This variability is unquestionably further enhanced by the fact that more and more CML patients are being diagnosed by chance (before they have become symptomatic) as part of a routine check-up that reveals an elevated white blood cell count.…”
Section: Spotlightmentioning
confidence: 99%
“…40 It is interesting that these findings add to the accumulating experimental evidence that certain mutations are sufficient to reactivate or confer self-renewal activity upon cells in which such programs had previously been thought to be normally extinguished. 38,39,41,[46][47][48] The anatomy of primitive elements in chronic phase CML clones…”
Section: Blast Crisismentioning
confidence: 99%